2020
DOI: 10.1111/1460-6984.12557
|View full text |Cite
|
Sign up to set email alerts
|

Maternal input to children with sex chromosome trisomies

Abstract: Background Although language difficulties are one of the most distinctive characteristics of the neuropsychological profile of children with sex chromosome trisomies (SCT), the analysis of the maternal input addressed to them is a neglected topic. Aims The present study aims to analyse the lexical, morphosyntactic, and functional features of the input addressed to children with SCT comparing them with those of the input directed to typically developing children (TD). Methods & Procedures Participants were 38 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 42 publications
2
21
2
Order By: Relevance
“…First, we compared the utterances produced by the mothers considering MLU and functional features because of the possible influence of these variables on the prosodic realisation. Our data showed no significant differences between the two groups, differently from what was found previously by Zampini et al (2020) with the same groups of participants. We hypothesise that the difference in the number of utterances considered in the analyses could be the reason for these different results.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…First, we compared the utterances produced by the mothers considering MLU and functional features because of the possible influence of these variables on the prosodic realisation. Our data showed no significant differences between the two groups, differently from what was found previously by Zampini et al (2020) with the same groups of participants. We hypothesise that the difference in the number of utterances considered in the analyses could be the reason for these different results.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, the prosodic features of the maternal input addressed to children with SCT appeared to be less favourable to enhancing children's language development than that of the input addressed to TD children. These data agree with the findings of our previous study (Zampini et al, 2020), which showed that the mothers of children with SCT tend to address them with a more demanding and directive style than the mothers of TD children. We interpreted these data hypothesising that the awareness that the children have a genetic syndrome, which will probably lead to linguistic problems, could influence the functional features of the maternal input addressed to them.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations